Iron Transport to Developing Ovules of Pisum sativum (I. Seed Import Characteristics and Phloem Iron-Loading Capacity of Source Regions). - Grusak, M. A. (1994)
To understand the processes that control Fe transport to developing seeds, we have characterized seed growth and Fe accretion and have developed a radiotracer technique for quantifying phloem Fe loading in vegetative source regions of Pisum sativum. In hydroponically grown plants of cv Sparkle, developing ovules exhibited a seed-growth period of 22 d, with Fe import occurring throughout the 22-d period. Average Fe content of mature seeds was 19 [mu]g. Source tissues of intact plants were abraded and pulse labeled for 4 h with 100 [mu]M 59Fe(III)-citrate. Fe was successfully phloem loaded and transported to seeds from leaflets, stipules, and pod walls. Total export of 59Fe from labeled source regions was used to calculate tissue-loading rates of 36, 40, and 51 pmol of Fe cm-2 h-1 for the leaflet, stipule, and pod wall surfaces, respectively. By comparison, surface area measurements, along with seed-growth results, allowed us to calculate average theoretical influx values of 42 or 68 pmol of Fe cm-2 h-1 for vegetative tissues at nodes with one or two pods, respectively. Additional studies with the regulatory pea mutant, E107 (a single-gene mutant of cv Sparkle that can overaccumulate Fe), enabled us to increase Fe delivery endogenously to the vegetative tissues. A 36-fold increase in Fe content of E107 leaves, relative to Sparkle, resulted in no increase in Fe content of E107 seeds. Based on these findings, we hypothesized that Fe is phloem loaded in a chelated form, and the expression/synthesis of the endogenous chelator is an important factor in the control of Fe transport to the seeds.